History economy and economic thought, as cognitive component for bachelors in KNUCA - Omelianenco, O.; Zinchenco, M. (Ways to Improve Construction Efficiency, 2015)
In the article the necessity and urgency methodological features of teaching the course "History of Economics and Economic Thought" are links with related economic and sociological sciences, describes the knowledge and skills of bachelors after studying the discipline.